2011
DOI: 10.1259/bjr/42762966
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary thin-section CT findings in acuteMoraxella catarrhalispulmonary infection

Abstract: Objective: Moraxella catarrhalis is an important pathogen in the exacerbation of chronic obstructive pulmonary disease. The aim of this study was to assess the clinical and pulmonary thin-section CT findings in patients with acute M. catarrhalis pulmonary infection. Methods: Thin-section CT scans obtained between January 2004 and March 2009 from 292 patients with acute M. catarrhalis pulmonary infection were retrospectively evaluated. Clinical and pulmonary CT findings in the patients were assessed. Patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 31 publications
1
6
1
Order By: Relevance
“…Other investigators have tried to demonstrate unique or specific findings on CT scans compared to plain radiography for particular pathogens. [11][12][13] We attempted to identify specific features of patients presenting with pneumonia that could assist clinicians in the decision-making process as it relates to ordering a CT scan. CT scans were performed more frequently on subjects who were younger, had lower severity of illness, and were admitted from the community.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have tried to demonstrate unique or specific findings on CT scans compared to plain radiography for particular pathogens. [11][12][13] We attempted to identify specific features of patients presenting with pneumonia that could assist clinicians in the decision-making process as it relates to ordering a CT scan. CT scans were performed more frequently on subjects who were younger, had lower severity of illness, and were admitted from the community.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, no past studies have compared the radiological findings of MC-CAP and SP-CAP. Okada et al [ 6 ] investigated 109 CT scans conducted on patients with M. catarrhalis pneumonia (only 34 of 109 patients had CAP) and found that the most common radiological findings were ground glass opacities (91%) followed by bronchial wall thickening (78%), centrilobular nodules (73%), and consolidation (49%). These findings were similar to our findings, suggesting that these findings are characteristic of M. catarrhalis respiratory infection regardless of the pneumonia classification as CAP or hospital-acquired pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous studies have not excluded patients co-infected with other respiratory bacteria, so the clinical features of MC-CAP isolated only M. catarrhalis by bacterial culture are unclear [ 4 , 5 ]. In terms of radiological features of MC-CAP, Okada et al [ 6 ] assessed pulmonary computed tomography (CT) findings in patients with acute M. catarrhalis pulmonary infection. However, 75 of 109 patients (68.8%) had nosocomial infection, and radiological findings of MC-CAP were not specifically described.…”
Section: Introductionmentioning
confidence: 99%
“…Although various bacterial factors such as surface components, the type III secretion system, quorum sensing, and scavenging of iron and other extracellular products has been reported (Sadikot et al, 2005;Williams et al, 2010), it is possible that the large amount of endotoxin derived from the pathogen led to excessive inflammation and resulted in systemic inflammatory response syndrome in the present case. Okada et al (2012) recently concluded from thin-section CT findings of 29 patients with P. aeruginosa pulmonary infection that ground-glass attenuation or bronchial wall S. Tsuji and others thickening were the main findings, but only nine patients with CAP were included in that study.…”
Section: Discussionmentioning
confidence: 99%